THE FORMATION OF COMMUNICATIVE COMPETENCE OF PRAGMATIC READING OF TEXTS AS A BASIS FOR INTERCULTURAL COMMUNICATION - Evdokiya I. Lobanova; Ekaterina V. Strijova; Alla B. Nisilevich (Статистика и экономика)
The purpose of the article is the study and evaluation ofthe use of pragmatic texts in the English language. The development of social and cultural relations requiresmodern person’s ability to participate in real intercultural communication. In this regard, one of the importantaspects of learning a foreign language becomes pragmatic.Pragmatics of foreign language communication beyondlanguage environment may be implemented in the classroomin English. The use of pragmatic text contributes to theformation of positive motivation of students to learn a foreignlanguage, as well as develops imagination and creativity.